1993
DOI: 10.1063/1.109634
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of coiled carbon fibers by pyrolysis of acetylene using a Ni catalyst and sulfur or phosphorus compound impurity

Abstract: Coiled carbon fibers were prepared by pyrolysis of acetylene activated using a Ni catalyst and a small amount of impurities at 600–800 °C. It was found that the addition of a small amount of sulfur or phosphorus compound impurities in acetylene was indispensable for the growth of coiled carbon fibers. Among the sulfur compounds used, thiophene was the most effective for growing coiled carbon fibers with uniform coil diameter and producing a high yield (about 50% coils). Similar results were obtained with phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…Also the co-pyrolysis of pyridine and Fe(CO) 5 as floating catalyst showed excellent result [15] and could even lead to vertically aligned helical carbon nanotubes (VAHCNTs) [16]. Sulfur has been shown to play a key role in enabling different catalyst, that under normal conditions are used for the growth of straight structures, to grow helical structures [11,17]. Motojima et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the co-pyrolysis of pyridine and Fe(CO) 5 as floating catalyst showed excellent result [15] and could even lead to vertically aligned helical carbon nanotubes (VAHCNTs) [16]. Sulfur has been shown to play a key role in enabling different catalyst, that under normal conditions are used for the growth of straight structures, to grow helical structures [11,17]. Motojima et.…”
Section: Introductionmentioning
confidence: 99%
“…al. studied helical CNTs in 1995 [8,9] but even earlier studies of helical structures can be found [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, unlike straight CNTs, coiled ones can show semi metallic properties beside the typical electrical characteristics of straight CNTs, such as exhibition metallic and semi conductive properties [7,8]. Almost simultaneously with claim that there is possibility about the existence of coiled CNTs with minimized energy confirmed by theoretical calculations [9][10][11] coiled carbon fibers were experimentally synthesized, principally from decomposition of hydrocarbons in the presence of metallic catalyst [12][13][14][15][16][17][18]. It is known that coiled CNTs are MWCNTs with incomplete crystalline structures created when paired pentagon-heptagon atomic rings arrange themselves periodically within the hexagonal carbon network.…”
Section: Introductionmentioning
confidence: 99%
“…16 In order to utilize nanometer scale structures in applications such as electronic, optoelectronic, and catalytic, bulk amounts of nanostructures will be required with tunable composition and structure. In this regard, bulk synthesis of semiconductor nanowires has been traditionally achieved using several variations of transition metal catalyzed techniques such as vapor-liquidsolid (VLS).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, bulk synthesis of semiconductor nanowires has been traditionally achieved using several variations of transition metal catalyzed techniques such as vapor-liquidsolid (VLS). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] In such techniques, the nanowire diameter is limited by the catalyst droplet size. However, creation of nanometer size catalyst droplets is a non-trivial task.…”
Section: Introductionmentioning
confidence: 99%